2023
DOI: 10.21608/jampr.2023.202016.1051
|View full text |Cite
|
Sign up to set email alerts
|

Cycadaceae: An Important Source for Biflavonoids and Various Pharmacological Effects of Different Cycas Species

Abstract: Cycadaceae is regarded as one of the largest cycad families. It is made up of 120 species of the single genus Cycas. Genus Cycas is found only in tropical and subtropical climates. They are dioecious plants with male and female reproductive cones. Members of Cycadaceae family are excellent suppliers of a wide range of beneficial phytochemicals however, only a few numbers of species had undergone phytochemical and pharmacological research. A wide battery of metabolites, including flavonoids, biflavonoids, pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
0
0
Order By: Relevance
“…Reports have shown that leaves of C. circinalis are used in the treatment of diabetes mellitus, and are also known to exude moderate antibacterial activity (Arshad et al, 2020;El-Seadawy et al, 2023). Despite these outlined ethnomedicinal uses, well-established scientific information is also available on cycads' toxicity, including C. circinalis.…”
Section: Introductionmentioning
confidence: 99%
“…Reports have shown that leaves of C. circinalis are used in the treatment of diabetes mellitus, and are also known to exude moderate antibacterial activity (Arshad et al, 2020;El-Seadawy et al, 2023). Despite these outlined ethnomedicinal uses, well-established scientific information is also available on cycads' toxicity, including C. circinalis.…”
Section: Introductionmentioning
confidence: 99%